2019
DOI: 10.1289/ehp3909
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Long-Term Exposure to Wind Turbine Noise on Redemption of Sleep Medication and Antidepressants: A Nationwide Cohort Study

Abstract: Background:Noise from wind turbines (WTs) is associated with annoyance and, potentially, sleep disturbances.Objectives:Our objective was to investigate whether long-term WT noise (WTN) exposure is associated with the redemption of prescriptions for sleep medication and antidepressants.Methods:For all Danish dwellings within a radius of 20-WT heights and for 25% of randomly selected dwellings within a radius of 20-to 40-WT heights, we estimated nighttime outdoor and low-frequency (LF) indoor WTN, using informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 34 publications
0
29
1
5
Order By: Relevance
“…This study did not support an association between wind turbine noise and redemption of antihypertension medication [107]. Poulsen et al [108] did find an association between outdoor wind turbine noise level and first redemption of sleep medication or antidepressants by people aged 65 years or older.…”
Section: Appendix: the Statistical Power Of Wind Turbine Noise Studiescontrasting
confidence: 58%
“…This study did not support an association between wind turbine noise and redemption of antihypertension medication [107]. Poulsen et al [108] did find an association between outdoor wind turbine noise level and first redemption of sleep medication or antidepressants by people aged 65 years or older.…”
Section: Appendix: the Statistical Power Of Wind Turbine Noise Studiescontrasting
confidence: 58%
“…A recent study [159] investigated the use of sleep and antidepressant medication by people living in the vicinity of wind farms. The authors found that the prevalence of prescription sleep medication purchase increased as the level of nighttime wind farm noise exposure increased.…”
Section: Sleep Disturbancementioning
confidence: 99%
“…Therefore, noise annoyance and sleep disturbance result from wind turbine operations are widely discussed as a potential health issue [4]. Studies conducted by Poulsen et al found that people over 65 years old are more likely to fill prescriptions for sleep medication when exposed to high levels of wind turbine noise [5]. This is further supported by another study from Abbasi et al claiming that noise exposure had a significant effect on general health, sleep disturbance, and annoyance of people living near wind farms [6].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Van Renterghem stated that wind turbine noises would become more annoying when mixed with local road traffic noise [9]. However, on the other side, a study funded by the Denmark government claimed that there is a lack of direct connection between cardiovascular disease (associated with short-term exposure) and wind turbine noise [5]. Despite that wind turbine noise might increase the risk of noise nuisances, the identification and validation of interactions between turbine noise exposure and symptoms (e.g., tinnitus, hearing loss, dizziness, and headache) still suffer from scientific evidence [10].…”
Section: Introductionmentioning
confidence: 99%